Mechanical groundnut thresher for farmers in Malaysia - Ahmad, Desa; Bardaie, M. Zohadie (1982)
Groundnut (Arachis hypogaea L) is one of the most important cash crops in Malaysia. Its production is on the rise. In certain rice growing areas, where double-cropping is not practiced, groundnut is the most popular off-season crop. The harvesting operation in the groundnut production process demands a substantial amount of labor when done manually. The agricultural sector in the country is currently facing an impending labor shortage due to the industrialization process which is being carried out by the Government. This labor shortage has caused a strain on the supply of labor during the harvesting period in groundnut production in the country. To overcome this problem, mechanization is being introduced in the country.